A rhinopristiform sawfish (Genus pristis) from the middle eocene (lutetian) of southern Peru and its regional implications - Collareta, Alberto (2020)
Modern sawfishes (Rhinopristiformes: Pristidae) are circumglobally distributed in warm waters and are common in proximal marine and even freshwater habitats. The fossil record of modern pristid genera (i.e., Pristis and Anoxypristis) dates back to the early Eocene and is mostly represented by isolated rostral spines and oral teeth, with phosphatised rostra representing exceptional occurrences. Here, we report on a partial pristid rostrum, exhibiting several articulated rostral spines, from middle Eocene strata of the Paracas Formation (Yumaque Member) exposed in the southern Peruvian East Pisco Basin. This finely preserved specimen shows anatomical structures that are unlikely to leave a fossil record, e.g., the paracentral grooves that extend along the ventral surface of the rostrum. Based on the morphology of the rostral spines, this fossil sawfish is here identified as belonging to Pristis. To our knowledge, this discovery represents the geologically oldest known occurrence of Pristidae from the Pacific Coast of South America. Although the fossil record of pristids from the East Pisco Basin spans from the middle Eocene to the late Miocene, sawfishes are no longer present in the modern cool, upwelling-influenced coastal waters of southern Peru. Given the ecological preferences of the extant members of Pristis, the occurrence of this genus in the Paracas deposits suggests that middle Eocene nearshore waters in southern Peru were warmer than today. The eventual disappearance of pristids from the coastal waters off southern Peru might be interpreted as reflecting the late Cenozoic trend of strengthening of the Humboldt Current.